37. DESCRIPTION OF EARLY RESULTS OF COMBINED SURGERY WITH PLATE SCREWS TO TREATMENT FRACTURES OF THE MIDDLE 1/3 CLAVICLE AT CAN THO CENTRAL GENERAL HOSPITAL, 2023 (Vietnam Journal of Community Medicine, 2024)
Background: Clavicle fusion surgery with screws is a popular surgery and is implemented in most orthopedic departments. To evaluate, analyze, learn from, and select effective treatment methods, we conducted this study. Objectives: Description of early results of surgical treatment of bone fusion with screws in patients with closed middle 1/3 clavicle fractures at Can Tho Central General Hospital in 2023.Research method: Retrospective description of 59 patients with closed middle 1/3 clavicle fractures undergoing bone fusion surgery with screws at Can Tho Central General Hospital from January 1, 2023 to December 31, 2023.Results: The group of patients with clavicle fractures is mainly men (81.4%), in the working age group 30 - 60 years old (69.5%), working as farmers/workers and the cause is common. The most common is traffic accidents (84.7%). The mechanism of injury is 69.5% of falls on hands and 30.5% of falls on shoulders. 98.3% had symptoms of swelling and pain, 39% of cases had bulging bones under the skin, 32.2% had shortened shoulders, 11.9% had drooping arms, and 10% had sharp pain and bone crunching. The majority of cases of clavicle fractures that were fused with a screw brace showed no displacement on X-ray (91.5%) and healed in the first stage of surgery (96.5%), with only a small percentage occurring. Complications such as slight displacement or superficial surgical wound infection. The rate of patients achieving good results is 91.5% and quite good is 8.5%.Conclusion: Clavicle fusion surgery with screws is quite good clinically and radiologically, with high success rate, short hospital stay and few complications. This is an effective treatment option for clavicle fractures.
Keywords: Fracture of middle 1/3 of clavicle, bone combination, screws.